Fintech, Sustainability and Financial Inclusion – Establishing the Link Among the Trio: A Research Model - Mr. Tuhin Siddharth; Dr. Rohit Kumar (The Bioscan, 2025)
This paper studies the impact of attitude towards fintech adoption on sustainable financial inclusion of a population in the extended TAM model. Judgmental sampling technique has been used for data collection using a structured self-administered questionnaire based on five-point Likert scale. The data collected is then statistically analysed using SPSS and AMOS software. Results reaffirmed that the independent variables like perceived usefulness, perceived ease of use, perceived social equity, responsible financial practices and trust have a positive impact on the attitude towards fintech adoption, which in turn has a significant positive impact on sustainable financial inclusion. Also, it was revealed that perceived risk has a significant negative impact on the attitude towards fintech adoption. These findings shall be helpful in policy and strategy formulation of the government and fintech firms in accordance to united nations sustainable development goals and world bank financial inclusion initiatives. The work is limited to a certain geography and do not include demographic characteristics like gender, income level, financial literacy, living conditions which may be further studied.